(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article comprehensively analyzes the theoretical foundations of advertising culture, its role in the marketing system and modern development trends. The study covers the socio-cultural aspects of advertising, ethical standards, mechanisms of influence on consumer consciousness and its transformation in the conditions of digital marketing on a scientific basis. It also analyzes the formation, level of development and existing problems of advertising culture in Uzbekistan, and suggests ways to improve it.